Strategi Pengembangan Branding Identitas Lokal Sebagai Pendorong Peningkatan Penjualan Produk UMKM - Agustin, Suci; Nurhayati, R; Wulan, Sry; Nur, Makmur Jaya; Is, Sitti Satriani (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Micro, Small and Medium Enterprises (MSMEs) are an important sector in the Indonesian economy, but often face challenges in improving product branding. This article discusses a community service project carried out by students and lecturers at Ahmad Dahlan Sinjai Islamic University in Lappacinrana Village, Sinjai Regency, South Sulawesi, from January to March 2024. This program aims to increase MSME players' understanding of branding strategies as a means of business expansion. Activities are carried out through direction, coaching and training with a participatory approach. The results show increased awareness of MSME participants about the importance of branding to strengthen product identity and increase competitiveness in the market. Participants are also able to design branding strategies according to the local characteristics of their products. This project makes a real contribution in empowering MSMEs as drivers of village economic growth and opens up market expansion opportunities for local products.